Nuove considerazioni sul disagio scolastico degli allievi - Fratini, Tommaso (Studi sulla Formazione/Open Journal of Education, 2024)
The article carries out some considerations on scholastic discomfort in our school, aiming to underline the importance of recovering this concept in pedagogical research. Starting from a historical excursus on the meanings and on some characteristics of the phenomenon over the decades, a possible definition of the concept is traced as a form of discomfort at the intersection of the profound pain of the adolescent, within his family events, with the pathologies of scholastic institution and the type of relationship established by the student with the teachers. On this basis, a typology of the forms of academic distress in our school is briefly outlined, placing emphasis on how much depressive and manic states of excitement interfere with the student’s ability to study profitably. The article concludes with a pedagogical reminder of the need to fully place human relationships at the center of school life and the development of students.